Enhancing Consumer Purchase Decisions: The Role of Servicescape, Content Marketing, and Experiential Marketing in Urban Street Food Businesses - Sagala, Alda Claudia; Afrizal, Afrizal; Nasution, Lisa Elianti; Manik, Desma Erica Maryati (International Journal of Economics Development Research (IJEDR), 2026)
The café business in Medan is rapidly growing, but increasing competition demands greater innovation in attracting consumers. Warkop & Fresh Milk Kakilima has experienced a decline in sales from 2021 to 2025, indicating a decrease in consumer purchase decisions. This is suspected to be influenced by suboptimal servicescape, content marketing, and experiential marketing, as supported by pre-survey results showing consumer dissatisfaction. Therefore, this study aims to analyze the influence of these three variables on consumer purchase decisions. The population in this study includes all consumers visiting Warkop & Fresh Milk Kakilima, whose exact number cannot be determined. Considering the uncertainty of the population size and the fluctuation of visiting consumers, the sample size was determined based on Hair’s recommendation. Therefore, the researcher decided to use 170 respondents as the research sample. The sampling technique applied is accidental sampling, which involves selecting respondents who are encountered by chance and are willing to participate. Based on the research results, it can be concluded that partially, servicescape, content marketing, and experiential marketing each have a positive and significant influence on purchase decisions at Warkop & Fresh Milk Kakilima Medan, as indicated by the t-value being greater than the t-table value. In addition, simultaneously, these three variables also have a significant effect on purchase decisions, as evidenced by the F-value being greater than the F-table value.